The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00540-016-2201-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and systemic toxicity of local anesthetics in children

Abstract: toxicity is 2-3 µg/ml of total (protein bound and unbound) and 0.1-0.2 µg/ml of unbound bupivacaine, levobupivacaine and ropivacaine [1,2]. Notably, the intra-arterial concentration of unbound bupivacaine for inducing CNS toxicity is approximately 50 % of unbound ropivacaine, both of which are three-and four-fold higher, respectively, than the intravenous concentration [1]. Cumulative case reports and animal experiments have also shown that the systemic toxicity of levobupivacaine and ropivacaine is less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 25 publications
(28 reference statements)
1
20
0
1
Order By: Relevance
“…Given the immature hepatic function in patients at this age, we believe that substituting this for the more commonly used aminoamide local anaesthetics may reduce these patients' risk of local anaesthetic toxicity. 9 We chose the infusion rate as it was published in several successful paediatric ESP catheter case reports, and it is a safe rate of chloroprocaine infusion. ESP catheter placement is feasible for premature neonates, and it provides effective intraoperative and postoperative analgesia for thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the immature hepatic function in patients at this age, we believe that substituting this for the more commonly used aminoamide local anaesthetics may reduce these patients' risk of local anaesthetic toxicity. 9 We chose the infusion rate as it was published in several successful paediatric ESP catheter case reports, and it is a safe rate of chloroprocaine infusion. ESP catheter placement is feasible for premature neonates, and it provides effective intraoperative and postoperative analgesia for thoracotomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, continuous ESP blocks may require large volume local anaesthetic infusions to be efficacious, which presents an additional challenge in this population due to immature hepatic metabolism and increased susceptibility to the cardiotoxic and neurotoxic effect of aminoamide local anaesthetics. 9 We present the novel management of a coagulopathic premature neonate undergoing thoracotomy for tracheoesophageal fistula (TEF) repair with a preoperatively placed ESP catheter with continuous intraoperative and postoperative chloroprocaine infusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have demonstrated that despite the similarities in estimated half-time, bupivacaine when delivered via modalities, such as epidural or caudal injections, persists in the serum for longer in infants and children than adults. [1718] This is due in part to the fact that infants have lower levels of alpha-1-acid glycoprotein in their serum, which is the primary protein that binds to bupivacaine. This can result in a higher free concentration of bupivacaine, placing an infant at a higher risk for toxicity.…”
Section: Pharmacokinetics In Infants/neonatesmentioning
confidence: 99%
“…Esto permite administrar menores dosis de anestésicos locales, proporcionar una adecuada propagación del anestésico y disminuir el riesgo de TSAL. Esto último sería más relevante en lactantes y recién nacidos, en quienes las variaciones farmacocinéticas y farmacodinámicas los hacen más propensos a desarrollar TSAL con concentraciones más bajas de anestésicos locales (Oda, 2016).…”
Section: Díaunclassified